Advancing the Safety, Health, and Well-Being of Commercial Driving Teams Who Sleep in Moving Semi-Trucks: The Tech4Rest Pilot Study. Issue 12 (December 2020) - Olson, Ryan; Johnson, Peter; Shea, Steven A.; Marino, Miguel; Rimby, Jarred; Womak, Kelsey; Wang, Fangfang; Springer, Rachel; Donovan, Courtney; Rice, Sean P.M.
Abstract : Objective: To test the feasibility, acceptability, and potential effectiveness of engineering and behavioral interventions to improve the sleep, health, and well-being of team truck drivers (dyads) who sleep in moving semi-trucks. Methods: Drivers ( n  = 16) were exposed to Condition A: a new innerspring mattress, and Condition B: a novel therapeutic mattress. A subsample of drivers ( n  = 8) were also exposed to Condition C: use of their preferred mattress (all chose to keep B), switching to an active suspension driver's seat, and completing a behavioral sleep-health program. Primary outcomes were sleep duration, sleep quality, and fatigue. Behavioral program targets included physical activity and sleep hygiene. Results: Self-reported sleep and fatigue improved with mattress A, and improved further with mattress B which altered vibration exposures and was universally preferred and kept by all drivers. Condition C improved additional targets and produced larger effect sizes for most outcomes. Conclusions: Results support these interventions as promising for advancing team truck drivers' sleep, health, and well-being.